Effect of Vitamin C as an Adjunct in Nonsurgical Periodontal Therapy in Uncontrolled Type 2 Diabetes Mellitus Patients - Kunsongkeit, Piyapat; Okuma, Nis; Rassameemasmaung, Supanee; Chaivanit, Pechngam (European Journal of Dentistry, 2019)
Objective The main purpose of this article is to evaluate periodontal parameters of chronic periodontitis patients with uncontrolled type 2 diabetes mellitus after initial periodontal therapy plus vitamin C.Materials and Methods A double-blind, placebo-controlled, clinical trial was conducted. Subjects received initial periodontal therapy plus 500 mg/day vitamin C for 2 months (n = 15) or placebo (n = 16). Fasting blood sugar (FBS), hemoglobin A1c (HbA1C), and plasma vitamin C level were assessed at baseline and 2 months post-treatment. Plaque Index, Sulcus Bleeding Index, Gingival Index, pocket depth, and clinical attachment level were measured at baseline, 1 month, and 2 months post-treatment.Results Almost all subjects had low level of plasma vitamin C at baseline. In the test group, plasma vitamin C was significantly increased to an adequate level at the end of 2 months. After periodontal treatment, FBS and HbA1c were not significantly different compared with baseline in the test group. In the control group, FBS was significantly decreased from baseline. However, no significant difference between groups was found either in FBS or HbA1c. All periodontal parameters were significantly improved from baseline in both groups. However, no significant difference was found between groups.Conclusion Supplementation of 500 mg/day vitamin C did not give an additional benefit in promoting periodontal status in periodontitis patients with uncontrolled type 2 diabetes mellitus.
Keywords: vitamin C; nonsurgical periodontal therapy; chronic periodontitis; uncontrolled type 2 DM